Interaksi Sosial Masyarakat Lawe Sigala-Gala Kabupaten Aceh Tenggara: Suatu Kajian Tentang Toleransi Antar Umat Beragama - Fauzi Ismail (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2017)
The harmony of religious life has a strong foundation in the life of society, whether historically empirical, ideological, constitutional, operational, or theologies and cultural. This is a strong capital to foster and foster harmony as a condition for the realization of unity in society. This paper attempts to explain the process of social interaction in community life in the sub-district of Lawe Sigala-Gala where a harmonious interrelationship between Muslim and non-Muslim communities has long been happening in their lives. Based on this fact has created harmonious harmony between the two followers of the religion.